2023
DOI: 10.1038/s41593-022-01242-y
|View full text |Cite
|
Sign up to set email alerts
|

Full protection from SARS-CoV-2 brain infection and damage in susceptible transgenic mice conferred by MVA-CoV2-S vaccine candidate

Abstract: The protective efficacy of vaccines against SARS-CoV-2 infection in the brain is yet unclear. Here, in the susceptible transgenic K18-hACE2 mouse model of severe COVID-19 disease, we report a detailed spatiotemporal description of the SARS-CoV-2 infection and replication in different areas of the brain. Remarkably, SARS-CoV-2 brain replication occurs primarily in neurons, producing important neuropathological alterations such as neuronal loss, incipient signs of neuroinflammation, and vascular damage in SARS-C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Moreover, the presence of alterations in cerebral blood vessels could be explained by direct infection by SARS-CoV-2 [193]. This was previously described in two different animal models, in which they observed that the SARS-CoV-2 nsp5 protein induces the cleavage of the essential modulator of NF-κB (NEMO) in infected endothelial cells, inactivating it.…”
Section: Cytopathic Effects On the Central Nervous Systemmentioning
confidence: 80%
See 3 more Smart Citations
“…Moreover, the presence of alterations in cerebral blood vessels could be explained by direct infection by SARS-CoV-2 [193]. This was previously described in two different animal models, in which they observed that the SARS-CoV-2 nsp5 protein induces the cleavage of the essential modulator of NF-κB (NEMO) in infected endothelial cells, inactivating it.…”
Section: Cytopathic Effects On the Central Nervous Systemmentioning
confidence: 80%
“…In addition, previous studies have reported that ventral brain blood vessels may undergo structural alterations in some patients with COVID-19, and morphological changes in microglia were also described. The latter, which are the result of microglial activation, are characterized by a retraction of the projections and an enlargement of the cell body, while alterations in cerebral blood vessels may appear as a consequence of an inflammatory activation of their permeability, which is also observed in other pathologies such as multiple sclerosis [193]. Regarding apoptosis in the dentate gyrus of the hippocampus, it has been previously described that certain infections affecting this region, such as bacterial meningitis, can also induce apoptosis, and learning deficits often occur in survivors [208].…”
Section: Cytopathic Effects On the Central Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible routes for SARS-CoV-2 invasion into the central nervous system (CNS) include: (1) entry through the nasal cavity to the olfactory bulb and subsequent spreading; (2) disruption of the BBB leading to leakage from blood vessels; and (3) retrograde transmission along neuronal axons. 33 Consequently, we analyzed the infection patterns of the variants in various brain regions and observed higher N proteinpositive signals in the olfactory bulb and cerebellum of Delta-infected brains (Figure 3B). Considering the spatial distance between the two regions, it appears unlikely that the virus originated from the olfactory bulb was directly transmitted to the cerebellum.…”
Section: Sars-cov-2 Variants-induced Brain Damage In Hace2 Micementioning
confidence: 99%